Guanzi : Political, Economic, and Philosophical Essays from Early China - Rickett, W. Allyn (Princeton Library of Asian Translations Ser., 1998)
Named for the famous Chinese minister of state, Guan Zhong (d. 645 B.C.), the Guanzi is one of the largest collections of ancient Chinese writings still in existence. With this volume, W. Allyn Rickett completes the first full translation of the Guanzi into English. This represents a truly monumental effort, as the Guanzi is a long and notoriously difficult work. It was compiled in its present form about 26 B.C. by the Han dynasty scholar Liu Xiang and the surviving text consists of some seventy-six anonymous essays dating from the fifth century B.C. to the first century B.C.The forty-two chapters contained in this volume include several which present Daoist theories concerning self-cultivation and the relationship between the body and mind as well as the development of Huang-Lao political and economic thought. The "Dizi zhi" chapter provides one of the oldest discussions of education in China. The "Shui di" chapter refers to the circulation of blood some two thousand years before the discoveries of William Harvey in the West. Other chapters deal with various aspects of statecraft, Yin-Yang and Five Phases thought, folk beliefs, seasonal calendars, and farming. Perhaps the best-known chapters are those that deal with various methods of controlling and stimulating the economy. They constitute one of the world's earliest presentations of a quantity theory of money. Throughout the text, Rickett provides extensive notes. He also supplies an introduction to the volume and a comprehensive index.